1998
DOI: 10.1074/jbc.273.24.14663
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cat3-mediated Cationic Amino Acid Transport Functionally Compensates in Cat1 Knockout Cell Lines

Abstract: Arginine transport is important for a number of biological processes in vertebrates, and its transport may be rate-limiting for the production of nitric oxide. The majority of L-Arg transport is mediated by System y ؉ , although several other carriers have been kinetically defined. System y ؉ cationic amino acid transport is mediated by proteins encoded by a family of genes, Cat1, Cat2, and Cat3. High affinity L-arginine transport was investigated in embryonic fibroblast cells derived from Cat1 knockout mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Thus, the up-regulation of CAT3 in fibroblasts lacking CD98hc is in accordance with increased AA ϩ intracellular content in such cells (Fig. 4A) as arginine, lysine, and histidine are substrates of murine CAT3 (22,23). Regarding the transport of AA 0 , by analyzing L-Ala uptake, we identified the presence of system A, a co-transporter of Na ϩ and neutral AAs, mainly excluding BCAAs and ARO AAs (24) (Fig.…”
Section: Cd98hc-associated Aa Transport Function Is Sufficient To Supmentioning
confidence: 98%
“…Thus, the up-regulation of CAT3 in fibroblasts lacking CD98hc is in accordance with increased AA ϩ intracellular content in such cells (Fig. 4A) as arginine, lysine, and histidine are substrates of murine CAT3 (22,23). Regarding the transport of AA 0 , by analyzing L-Ala uptake, we identified the presence of system A, a co-transporter of Na ϩ and neutral AAs, mainly excluding BCAAs and ARO AAs (24) (Fig.…”
Section: Cd98hc-associated Aa Transport Function Is Sufficient To Supmentioning
confidence: 98%
“…Previous studies have reported that the expression of CAT-2 mRNA and CAT-3 mRNA and protein were compensatorily upregulated in embryonic fibroblast cells derived from CAT-1 knockout mice. 22 Moreover, other cationic transport systems, ie, system b 0,ϩ and yϩL, have been shown to exist in the mammalian kidney 23,24 and may also contribute to L-arginine uptake in NO-producing cells. A further possibility is that the cationic amino acids have a dual effect on L-arginine: (1) they may competitively inhibit L-arginine uptake by cationic amino acids (cis-inhibition) and (2) the cationic amino acids may also facilitate the exodus of intracellular L-arginine from cells via system y ϩ (transstimulation) and thereby deplete the cells of L-arginine.…”
Section: Hypertension February 2002mentioning
confidence: 99%
“…Prior to RNA preparation, macrophages were incubated in the presence or absence of 20 units ml Ϫ1 IFN␥ (Sigma) for 2 h followed by the addition of 100 ng ml Ϫ1 LPS (Escherichia coli 055:B5, Sigma) to the primed cells for an additional 6 h. 10 g of tissue or 5 g of macrophage RNA was analyzed with Cat1, Cat2, and glyceraldehyde-3-phosphate dehydrogenase probes (26). A 1.3-kilobase BstX1/XhoI fragment of Cat3 was isolated for random-prime labeling (26).…”
Section: Generation Of Cat2mentioning
confidence: 99%
“…Prior to RNA preparation, macrophages were incubated in the presence or absence of 20 units ml Ϫ1 IFN␥ (Sigma) for 2 h followed by the addition of 100 ng ml Ϫ1 LPS (Escherichia coli 055:B5, Sigma) to the primed cells for an additional 6 h. 10 g of tissue or 5 g of macrophage RNA was analyzed with Cat1, Cat2, and glyceraldehyde-3-phosphate dehydrogenase probes (26). A 1.3-kilobase BstX1/XhoI fragment of Cat3 was isolated for random-prime labeling (26). The NOS2 cDNA probe was cloned by RT/PCR from mouse mammary tumor cDNA using the primers 5Ј-CAG TGC CCT GCT TTG TGC GAA GT-3Ј and 5Ј-AAC GTT TCT GGC TCT TGA GCT GGA A-3Ј; the product then was ligated into the vector pGEM-T Easy (Promega), and the sequence was verified using flanking T7 and SP6 primers.…”
Section: Generation Of Cat2mentioning
confidence: 99%
See 1 more Smart Citation